Intellectual property issues in software (National Academy P. WashingtonUS, 1991)
Discusses some of the changing technical, economic and legal circumstances that underlie the debate over the adequacy of intellectual property protection for software. Describes the underlying tenets of US copyright, patent and trade secret laws, also discusses international treatment of software as intellectual property. Examines the attributes of software, the nature of the process for designing and developing software, and the relevance of both to determining which elements of software merit protection. Looks at legal uncertainties and how software firms are responding to these uncertainties.
Bibliography: p. 95-97